An efficient group key agreement scheme for UAV swarms - Wang, Zhe; Li, Jing; Yuan, Shengzhi; Zhang, Yinuo (Frontiers in Physics, 2026)
Unmanned Aerial Vehicle (UAV) group communication plays a crucial role in collaborative UAV operations, yet its security faces numerous challenges. Authentication and key agreement protocols, as core technologies for securing UAV communications, have significant research value. In the context of UAV group communication, this paper introduces a dynamic authentication and group key negotiation protocol leveraging elliptic curve signature techniques. By incorporating group key agreement techniques, the proposed protocol offloads complex key computation tasks to the cluster controller, thereby effectively alleviating the problem of limited UAV computational resources and significantly improving overall system efficiency. The proposed protocol supports dynamic joining and leaving of UAV groups, ensuring essential security properties such as backward secrecy and forward secrecy, thus guaranteeing the security and adaptability of group communication. Based on the random oracle model, this paper employs formal security proofs to verify the protocol’s security and further demonstrates through informal security analysis that it can effectively resist both active and passive attacks. Performance evaluation results show that the proposed protocol outperforms existing schemes in terms of computational and communication overhead, achieving both efficiency and security, making it suitable for resource-constrained UAV group communication environments with broad application prospects.